Reologiczna Teoria Wytrzymałości i Jej Zastosowanie do Betonu - Eimer, C. (Engineering Transactions, 1963)
This strength theory is based on the assumption that the body is composed of a great number of rheologic elements located in space (Fig. 2) and having definite strength properties constituting random variables with known probability distribution. This assumption concerns both rheologic and strength properties and takes into consideration the fundamental fact that strength concentrations in the remaining parts of the body increase as structural microdefects increase and that the destruction has the character of a «chain» process. The case of constant strain rate and constant stress are considered in detail, it being shown that there exists a close relation between them. It is shown that there exists a durable strength (lower than the immediate one) below which destruction is not possible. Above this value, it takes place with a certain delay. Equations determining this strength and the failure delay are obtained as well as those describing the strain process in function of time. The applicability range of the linear creep theory is discussed. The results are obtained in a closed form convenient for numerical computation and direct practical use. They are applied to concrete and confronted with the tests of H. R.ÜSCH, [2] showing a very good agreement. Certain numerical results are given for comparison.